2013
DOI: 10.1371/journal.pone.0055839
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effect of Kaempferol Glycosides against Brain Injury and Neuroinflammation by Inhibiting the Activation of NF-κB and STAT3 in Transient Focal Stroke

Abstract: BackgroundIschemic brain injury is associated with neuroinflammatory response, which essentially involves glial activation and neutrophil infiltration. Transcription factors nuclear factor-κB (NF-κB) and signal transducer and activator of transcription 3 (STAT3) contribute to ischemic neuroinflammatory processes and secondary brain injury by releasing proinflammatory mediators. Kaempferol-3-O-rutinoside (KRS) and kaempferol-3-O- glucoside (KGS) are primary flavonoids found in Carthamus tinctorius L. Recent stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
100
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(107 citation statements)
references
References 34 publications
(37 reference statements)
3
100
0
4
Order By: Relevance
“…STATs are a family of transcription factors involved in many cellular activities [32]. It has been reported that STAT3 activation was found in numerous cell types in the brain including neurons, astrocytes, microglia, endothelial cells, monocytes and macrophages, involving in neuronal development, neuroprotection, and regeneration after ischemic injury [33,34,35]. Perez-Pinzon et al have demonstrated phosphorylation and nuclear translocation of STAT3 in response to preconditioning by OGD in mixed cortical-glial co-cultures [36].…”
Section: Discussionmentioning
confidence: 99%
“…STATs are a family of transcription factors involved in many cellular activities [32]. It has been reported that STAT3 activation was found in numerous cell types in the brain including neurons, astrocytes, microglia, endothelial cells, monocytes and macrophages, involving in neuronal development, neuroprotection, and regeneration after ischemic injury [33,34,35]. Perez-Pinzon et al have demonstrated phosphorylation and nuclear translocation of STAT3 in response to preconditioning by OGD in mixed cortical-glial co-cultures [36].…”
Section: Discussionmentioning
confidence: 99%
“…In experimental rat models, naringenin (50 mg/kg ip for 21 days) (Raza et al, 2013) or kaempferol glycosides from Carthamus tinctorius L. (7.5 or 10 mg/kg i.v. acute) showed a beneficial impact on neuroinflammation by inhibiting STAT3 and NF-κB after ischemic brain injury in rat (Yu et al, 2013).…”
Section: Mechanisms Of Action Of Flavonoids In Controlling Neuroinflamentioning
confidence: 94%
“…In high fat fed C57Bl/6 mice supplemented with luteolin (10mg/kg) for 16 weeks, spatial memory was improved along with a decreased expression of inflammatory markers TNF-α, IL-1β, IL-6 and NF-kB, oxidative stress and neuronal insulin resistance, and an increased production of BDNF and synaptic proteins . Accordingly, kaempferol-3-O-rutinoside (10 mg/kg) and kaempferol-3-Oglucoside (7.5 mg/kg) significantly inhibited the level of IL-1β, iNOS, ICAM-1 and the metallopeptidase 9 (MMP-9) in ischemic brain-injured rats (Yu et al, 2013). Furthermore, oral administration of scuttelarin (5 or 20 mg/kg), a flavone extracted from Erigeron breviscapus, decreased the hypertension-induced expression of NF-κB, TNF-α, IL-1β and IL-18 in the cortex and the striatum of rat.…”
Section: Mechanisms Of Action Of Flavonoids In Controlling Neuroinflamentioning
confidence: 97%
“…For example, fisetin (0.05%, 6 months) reduced the protein expression of inflammatory markers in huAPPswe/PS1DE9 transgenic mice in an ERK-p25-mediated pathway without affecting the mRNA expression of NF-kB1 (Currais et al, 2014). Similarly, kaempferol-3-O-rutinoside (10 mg/kg) and kaempferol-3-O-glucoside (7.5 mg/kg) reduced the neuroinflammatory response by inhibiting signal transducer and activator of transcription 3 (STAT3) and NF-kB following an ischemic brain injury in rats (Yu et al, 2013). In addition, intervention trial with an anthocyanin extract from blueberries (300 mg/d for 3 weeks) significantly reduced the plasma concentration of NF-kB-related proinflammatory cytokines and chemokines (IL-4, IL-13, IL-8 and IFN-a) in a group of 120 men and women aged 40-74 years (Karlsen et al, 2007).…”
Section: Polyphenols Mitigate Neuroinflammationmentioning
confidence: 99%